The ecosystem of human capital in care homes - Kejžar, Anamarija; Turunen, Katri Maria (Frontiers in Public Health, 2024)
This qualitative study delves into the essential yet often overlooked experiences of knowledge transfer within care homes (CH). Conducted in a Slovenian CH in 2020 and 2023, participants, including CH management, staff, and residents with their relatives, shared perceptions of knowledge transfer at various levels. The study aims to explore barriers and facilitators for knowledge transfer crucial for creating new knowledge, services, and enhancing care quality for older adults. Structured focus group interviews were conducted, and data were collected within the CH. The participants' insights into knowledge transfer were probed, covering various dimensions such as between individuals, groups, organizations, and the community. Transcriptions of recorded interviews were analyzed using content analysis. Knowledge transfer within the CH was facilitated through continuous training, diverse communication channels, and mentoring. Collaboration with relatives improved understanding of resident preferences, habits, and overall enhanced the quality of care. This collaborative effort allowed mutual learning and knowledge transfer from the CH to the broader community. Barriers were identified in the form of stereotypical attitudes towards aging and care, further reinforced by negative news coverage on older adult's care. The multidimensional nature of knowledge in CH centers on resident well-being, emphasizing three key aspects of knowledge transfer: between staff and residents, staff and residents' families, and between the CH and the community. In the context of age management, creating opportunities for knowledge transfer is crucial, emphasizing a transition from traditional institutional care to an approach prioritizing knowledge about quality care and involving experts from experiences in care process.